Video Laryngoscopy for Endotracheal Intubation: A Consideration for Manual In-Line Stabilization Without Cervical Collar Versus Full Immobilization - Aramvanitch K; Leela-Amornsin S; Tienpratarn W; Nuanprom P; Aussavanodom S; Yuksen C; Boonsri S; Boonjarus N; Sanepim S (Therapeutics and Clinical Risk Management)
Kasamon Aramvanitch,1 Sittichok Leela-Amornsin,2 Welawat Tienpratarn,1 Promphet Nuanprom,1 Supassorn Aussavanodom,1 Chaiyaporn Yuksen,1 Sirinapa Boonsri,1 Natcha Boonjarus,1 Somchoak Sanepim1 1Department of Emergency Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakan, ThailandCorrespondence: Sittichok Leela-Amornsin, Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakan, Thailand, Email sittichok.lee@mahidol.ac.thIntroduction: Traumatic patients with cervical spine motion restriction have difficulty with endotracheal intubation (ETI) due to the limitations of neck movement and mouth opening. Nevertheless, the removal of the cervical collar for ETI in a prehospital setting may lead to a deterioration in neurological outcomes. This study compares the success rate of ETI utilizing a video laryngoscope (VL) on a manikin, contrasting manual in-line stabilization (MILS) without a cervical hard collar against full immobilization.Methods: A randomized, non-crossover study was conducted involving 56 paramedic students assigned by SNOSE to utilize various box sizes for VL intubation with MILS without a cervical hard collar or full immobilization technique on a manikin. The primary outcome was the intubation success rate. Secondary outcomes included attempts, time for successful intubation, and Cormack-Lehane classification.Results: Fifty-six participants were evaluated; 28 were in the full immobilization group, and another 28 were in the MILS without cervical hard collar group. Baseline characteristics showed no difference between both groups. The success rate of VL intubation showed no difference between the full immobilization group and the MILS without a cervical hard collar group (28 [100%] vs 28 [100%]; 24 [85.71%] vs 27 [96.43%] on first attempt; 4 [14.29%] vs 1 [3.57%] on second attempt; p-value 0.352). Time required to perform successful intubation (median [IQR] 17.20 [12.53, 24.40] vs 17.53 [14.06, 23.73], p-value 0.694) and Cormack-Lehane classification (11 [39.29%] vs 10 [35.71%] in grade I; 16 [57.14%] vs 17 [60.71%] in grade II; 1 [3.57%] vs 1 [3.57%] in grade III, p-value 1.000) showed no statistical difference between the two groups.Conclusion: It is unnecessary to remove the cervical hard collar when performing endotracheal intubation while using a video laryngoscope.Keywords: video laryngoscope, full immobilization, success rate, endotracheal intubation